1979
DOI: 10.1029/ja084ia02p00513
|View full text |Cite
|
Sign up to set email alerts
|

The near‐wake structure of the Atmosphere Explorer C (AE‐C) Satellite: A parametric investigation

Abstract: Measurements of ion current, electron temperature, and values of space potential obtained from the cylindrical electrostatic probe on board the Atmosphere Explorer C (AE-C) satellite were used to examine, in a parametric manner, the angular distribution of charge around the satellite. Interest is focused on nighttime equatorial data in the altitude range 275-620 km, which yields a wide range for the parameter RD (=Ro/)ko, where Ro is the radius of the satellite and 3,0 is the ambient value of the Debye lengths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…for RD • 10-102 [Samir et al, 1979 In this paper we examine some recent results obtained from low-energy particle probes mounted on the Orbiter Columbia during the STS 3 mission and compare them with results from small ionospheric satellites. Of specific interest will be the comparison of interaction characteristics such as…”
Section: While Some Experimental Information Is Available For the Varmentioning
confidence: 96%
See 2 more Smart Citations
“…for RD • 10-102 [Samir et al, 1979 In this paper we examine some recent results obtained from low-energy particle probes mounted on the Orbiter Columbia during the STS 3 mission and compare them with results from small ionospheric satellites. Of specific interest will be the comparison of interaction characteristics such as…”
Section: While Some Experimental Information Is Available For the Varmentioning
confidence: 96%
“…However, such errors are relatively small and definitely much smaller than an order of magnitude. This was discussed in the works bySamir et al [ 1979. The Sarnir et al[ 1980] study was concerned with ions and not with electrons and, as is known, the electron flux differs significantly from the ion flux in the maximum wake position[S amir et al, 1973], as shown inFigure 6.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…A dielectric coating was applied to one side of the plate made of aluminum (length l = 45 cm, width 2R = 16 cm, and thickness δ ≈ 0.1 cm). An aluminum coating was applied (sprayed) onto the surface of the disk (made of quartz) 15 [4] for Sei ≈ 8, R ds ≈ 40, and −Φw ≈ 0 (5) and 20 (6); points 7-9 are the results measured in [12] in the ionosphere on the Explorer-C (AE-C) artificial satellite for 5.9 Sei 8.04, −Φw ≈ 10, and R ds ≈ 116.3 (7), 135.7 (8), and 162.5 (9); points 10 are the results measured in [13] in the ionosphere on the S3-2 artificial satellite for Sei ≈ 8, R ds 45, and −Φw ≈ 10; points 11 are the results measured in [14] in the wake behind the Space Shuttle for Sei ≈ 3.35 and R ds 2 · 10 3 ; (b) angular distribution of ion density nis(θ) at t = 0.192: points 1 are the results measured in [12] on the Explorer-C (AE-C) artificial satellite for Sei ≈ 7.83, R ds ≈ 73.4, −Φw ≈ 8.8, and ξei = 1.14; points 2 are the results measured in the present work (wake behind a cylinder for Sei ≈ 5.1, R ds ≈ 78, −Φw ≈ 6.7, and ξei = 4); curve 3 is the solution of Eq. (7) with the dependence nis(Φ) from [6] for Sei ≈ 5.1, R ds ≈ 80, and −Φw ≈ 6.7; points 4 are the results of the discrete flow model [11].…”
Section: High-voltage Charging Of the Leeward Surfaces Of A Solid By mentioning
confidence: 99%
“…Singh et al (1987) and Samir et al (2001) demonstrated that the electrons and ions are heated in the wake, while Siskind et al (1984) also observed an electron heating in the ram direction. Henderson and Samir (1967) measured the current depletion in the wake with respect to the ram and Samir et al (1979 studied the asymmetry in the current distribution in the wake. Oran et al (1974) observed the increasing of the density in the near-wake region.…”
Section: Introductionmentioning
confidence: 99%